KINERJA KELEMBAGAAN TERHADAP DISTRIBUSI PUPUK BERSUBSI (STUDI KASUS PADA GAPOKTAN SEPAKAT DI DESA PATTINOANG KECAMATAN GALESONG KABUPATEN TAKALAR) (JURNAL AGRIBISNIS TERPADU, 2022)
Gapoktan as a socio-economic organization aims to increase economies of scale and business efficiency. The Gapoktan institution in Pattinoang Village is one of the most important parts in managing the formulation of the distribution of subsidized fertilizers. However, the process of distributing subsidized fertilizers must be initiated by the proposed fertilizer needs of the farmers as outlined in the RDKK (Definitive Plan for Group Needs). The sampling technique used is purposive sampling. The results showed that (1) The institutional performance of the Association of Farmer Groups (Gapoktan) agreed on the distribution of subsidized fertilizers in Pattinoang Village, Galesong District, Takalar Regency, in the high category with an average of 81.8. of 3 variables based on the quantity of subsidized fertilizer, service quality and timeliness of distribution. (2) The distribution pattern of subsidized fertilizer in Pattinoang village on time according to the concept of the Definitive Plan for Group Needs (RDKK) is not implemented properly and its implementation has not been implemented in accordance with the guidelines for implementing subsidized fertilizer subsidies from the government.